Mesenchymal Stem Cells Promote the Osteogenesis in Collagen-Induced Arthritic Mice through the Inhibition of TNF-α - Chang Liu; Huayong Zhang; Xiaojun Tang; Ruihai Feng; Genhong Yao; Weiwei Chen; Wenchao Li; Jun Liang; Xuebing Feng; Lingyun Sun (Stem Cells International)
Objective. To investigate the effects of umbilical cord mesenchymal stem cell (UC-MSC) transplantation on joint damage and osteoporosis in collagen-induced arthritis (CIA) mice and to explore the mechanisms by which UC-MSCs modulate the osteogenic differentiation. Methods. CIA mice were divided into the following treated groups: UC-MSC transplantation group, antitumor necrosis factor- (TNF-) α group, and zoledronic acid (ZA) group. Microcomputed tomography (micro-CT) was used to analyze the bone morphology parameters. Osteogenic differentiation of treated CIA mice was determined. Bone marrow mesenchymal stem cells (BM-MSCs) from CIA mice were treated with TNF-α in vitro to explore their effects on osteogenesis. Results. The arthritis score was significantly reduced in the UC-MSC transplantation and anti-TNF-α-treated CIA groups, compared with control mice (P<0.001). Micro-CT showed that CIA mice developed osteoporosis at 12 weeks after immunization. The bone morphology parameters were partially improved in UC-MSC-treated CIA mice. Impaired osteogenic differentiation functions were indicated by decreased ALP activity (P<0.001) and reduced mRNA and protein levels of osteogenic marker genes (P<0.05) in CIA mice compared with DBA/1 mice. UC-MSC treatment significantly upregulated the impaired osteogenic differentiation ability in CIA mice. Meanwhile, the serum TNF-α level was decreased significantly in the UC-MSC group. The osteogenesis was reduced with the addition of TNF-α in vitro. Conclusion. This study demonstrated that UC-MSC transplantation not only significantly improved the joint damage but also played a beneficial role in osteoporosis in CIA mice. Mechanistically, the improved osteogenic differentiation of CIA under UC-MSC treatment may be achieved by inhibition of TNF-α.